1998
DOI: 10.1103/physrevb.58.5189
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-isotope effect of the paramagnetic-insulating to ferromagnetic-metallic transition inLa1xCax

Abstract: The oxygen-isotope effect of the ferromagnetic transition in La 1Ϫx Ca x MnO 3 was investigated from x ϭ20% to xϭ43%. This is the range of the conducting ferromagnetic phase. We find that ␣ O ϭ Ϫ⌬ ln T c /⌬ ln m decreases from 0.36 to 0.14 with increasing Ca concentration. A large value of ␣ O ϭ0.83 was found for xϭ20%, it is possibly connected with excess oxygen content. The isotope effect decreases with increasing tolerance factor, pointing to the importance of double exchange. The isotope effect at 35% Ca i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
60
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 35 publications
(28 reference statements)
8
60
1
Order By: Relevance
“…2 and Eqs. (11), (12) suggest that the diagrams Σ 1b and Σ 1c can be absorbed in a γ-dependent λ c as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and Eqs. (11), (12) suggest that the diagrams Σ 1b and Σ 1c can be absorbed in a γ-dependent λ c as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations in several classes of "strongly correlated" materials (high-temperature superconductors, "colossal magnetoresistance" manganites, and alkalimetal doped C 60 ) of large isotope effects on electronic properties, including electron effective mass 4-8 and superconducting, 4-9 magnetic, [10][11][12][13] and charge ordering [14][15][16][17] transition temperatures pose a fundamental challenge to this understanding and call for a theory that goes beyond ME. Some authors 6,7,10,12 have attempted to relate their experimental data to formulas derived for the case of a "polaron": a single electron interacting with lattice deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The region that looks most affected by oxygen isotope substitution at these temperatures is between 20 and 40 meV where the scattering intensity near 30 meV is lower for the 18 O sample than the 16 O sample. Raman measurements by Franck et al 51 near 0 K showed that the oxygen modes at 28 meV and 53 meV are shifted downward by 1 meV and 2.6 meV for the 18 O sample. At low temperatures (inset) there does seem to be a difference in the spectra at 68 meV where the 16 O peak may be slightly higher and more clearly defined.…”
mentioning
confidence: 99%
“…12 the observed oxygen isotope effect has been partially attributed to different oxygen stoichiometry. 51 For the present samples the high resolution powder diffraction measurements could be used to establish that the oxygen contents for both samples were identical within experimental uncertainties, and thus there can be no significant variation in T C due to the total oxygen content. The lattice parameters, average atomic positions and occupancies were identical as well.…”
mentioning
confidence: 99%
“…They are La 1−x Ca x MnO 3 [18,19], Pr 1−x Ca x MnO 3 [20], RuSr 2 GdCu 2 [21], ZrZn 2 [22] and SrRuO 3 [23]. First three compounds La 1−x Ca x MnO 3 , Pr 1−x Ca x MnO 3 and RuSr 2 GdCu 2 show that T c decreases upon the isotope substitution 16 O→ 18 O.…”
Section: Introductionmentioning
confidence: 99%